PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN DENGAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE SEBAGAI VARIABEL INTERVENING - ASTUTI, KURNIASIH DWI; KUSUMADINI, MERLIANI (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2016)
This study aimed to analyze the influence of corporate governance on financial performance with corporate social responsibility disclosure as an intervening variable. Corporate governance is measured by an index that has been developed komsiyah, financial performance in proxied by Return On Asset and corporate social responsibility disclosure is proxied by the GRI index. The sample in this study are as many as 30 companies, and samples used in this study is a manufacturing company listed on the Indonesia Stock Exchange during 2010-2014. The statistical method used is regression analysis with path analysis. Based on the test results showed that corporate governance has positive effect and significant on financial performance. Corporate Governancehas positive effect and significant on corporate social responsibility disclosure. Corporate social responsibility disclosure haspositive effect and significant onfinancial performance and corporate social responsibility disclosure mediate the association of corporate governance and financial performance  Keywords: Corporate Governance, Corporate Social Responsibility Disclosure, Financial Performance,  Return On Asset